Cardiac Physiology of Polar Bears in Winter Dens - Folk, G.E.; Brewer, M.D.; Sanders, D. (ARCTIC, 1970)
Results of winter 1967-68 and 1968-69 measurements by radio-capsules implanted in two polar bears indicate that this species is capable of reducing circulatory activity in dormancy in the same way as the grizzly and black bear. Sleeping heart rates of initially 60 beats/min changed slowly week by week to 27/min.